ANALISIS YURIDIS EMPIRIS OPTOMETRY DISPUTES DAN MALPRAKTIK OPTOMETRI DI INDONESIA - Riono, YV Agung; Simarmata, Murni Marlina; Efendi , Zakaria; Doringin , Ferry (Jurnal Mata Optik, 2026)
This research conducts a normative and empirical legal analysis of optometry disputes and malpractice in Indonesia, framed through the IRAC method (Issue, Rule, Application, Conclusion) and contrasted with global practices. The Issue is whether optometrists, as formally recognized health professionals under Health Law No. 17 of 2023, may incur criminal liability for malpractice, and how such liability differs from civil optometry disputes. The Rule derives from Indonesian statutes, Health Law 2023, Consumer Protection Law 1999, KUHP 2025, and KUHAP 2026, which establish criminal sanctions for negligence causing serious injury or death, while consumer law governs disputes over service quality. The Application reveals that most Indonesian cases are optometry disputes, involving refractive errors that rarely result in blindness or death, and are resolved through civil remedies under consumer protection. Malpractice liability arises only when negligence leads to severe outcomes, requiring expert testimony and prior review by the Professional Discipline Council of Health (Majelis Disiplin Profesi Kesehatan). In comparative perspective, jurisdictions such as the United States and the United Kingdom emphasize civil liability and professional disciplinary mechanisms, reserving criminal sanctions for egregious negligence. Indonesia’s dualistic framework, criminal liability for malpractice and civil remedies for disputes, which reflects both global trends and local statutory innovations. The Conclusion underscores the strategic role of professional organizations (IROPIN) and business associations (GAPOPIN) in prevention through standard-setting, advocacy, and mediation. Strengthening these mechanisms is essential to harmonize Indonesian practice with international norms, ensuring accountability, consumer protection, and professional integrity.